Inconsistent trends between early and late winters in extreme cold events in China from 1980 to 2021 - Dong, Wei; Zhao, Liang; Cheng, Wei; Guo, Chunyan; Shen, Xinyong; Yao, Haoxin (Frontiers in Environmental Science, 2022)
Understanding intra-seasonal variation in extreme cold events (ECEs) has important implications for climate prediction and climate adaptation. However, the ECEs difference between early ( from December 1 to January 15) and late (from January 16 to February 28) winters is a lack of sufficient understanding. Herein, we investigated the trends of ECEs over eastern China in early and late winters. Results showed that the number of days with ECEs had a faster and uniformly decreasing trend in late winter over eastern China, whereas the decreasing trend in early winter was not significant because of the dipole pattern with an increase of ECEs in northeast China and a decrease of ECEs in southeast China during the time period 1980–2021. This denoted that China was presenting a pattern of “cold early winter–warm late winter”. The feature of cold early winter was related to a significant increase in high-latitude blocking highs extending poleward and reaching the Arctic Circle in early winter during the last 20 years. In particular, there was a large-scale tilted high ridge from the Ural Mountains to northern Asia, which favored the negative phase of the Arctic oscillation. This, in turn, led to a strong Siberian high and East Asian winter monsoon. Strong cold advection related to the circulation anomalies caused an ECEs increase in northeast China and dominated the change in temperature over eastern China in early winter. By contrast, the decrease in ECEs in late winter in the last 20 years was more related to the interdecadal enhancement of the anticyclonic anomaly over the north Pacific (NPAC). The strong NPAC extended to East Asia in a zonal direction, causing strong warm anomalies in eastern China through warm advection and diabatic heating, which weakened the northerly and prevented the East Asian trough from moving south, resulting in a warmer East Asia and a uniform decrease in late winter.